Anxiety reducing through a neurofeedback serious game with dynamic difficulty adjustment - Mata, Luís Miguel Almeida da (2018)
Presently, society has to deal with a large number of mental issues. Anxiety disorder is a serious concern, affecting millions of people’s lives and, although methods to tackle the problem currently exist, these main treatments are being linked to some issues and improvements must be found. One of the alternatives is Neurofeedback, a biofeedback treatment, completely non-invasive and showing impressive results so far. It uses a neuroheadset equipment to read the neural activity of the brain, giving the user visual feedback about it. The purpose this, is to train the users’ brain in specific regions and frequencies, allowing the subjects to learn how to voluntarily control its neural activity, even outside of the session. Current applications using this method might be too simple, which can become tedious and disengaging. Serious games can help with these issues, since it can bring enjoyment and engagement while doing this type of treatment. The interest in games’ capabilities in education has been increasing over the past years, since it has been proved that games are an excellent tool for education and skill learning. Joining these concepts of game and neurofeedback, this project aims to create a serious game prototype, applying the current treatment knowledge. The development process of a new game with neuroheadset integration, capable of reading the neural activity of the user while playing and giving the appropriate feedback, will be described in the present document. Since studies proved that a good balance between challenge and skill increases the learning performance, a dynamic difficulty adjustment system is implemented within the game, allowing the game to adapt itself to each user’s skill individually, and keeping the user in a challenging, motivating zone. At the end of the document, the results of pilot test on a few subjects are shown.